PENGARUH FINANCIAL DISTRESS DAN CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Rony Hermawan; Titik Aryati (Jurnal Ekonomi Trisakti, 2022)
This research aims to examine the effect of financial distress and corporate governance on tax avoidance. Tax avoidance is measured using cash effective tax rate (CETR), while financial distress is measured using Altman Z-Score, and corporate governance is proxied by independent commissioners, board of directors, and audit committee. Quantitative methods used in this research by using secondary data sources. Researchers took the data on the company from 2018 to 2020 and using the analysis unit manufacturing companies consumer goods sector listed on the Indonesia Stock Exchange. The method of determining the sample in this research used purposive sampling. Analysis of the data used as hypothesis testing is multiple regression analysis. The results of this research indicate that financial distress, independent commissioners, and board of directors have a negative effect on tax avoidance. Meanwhile, audit committee have a positive effect on tax avoidance.